LipidXplorer: Software for Quantitative Shotgun Lipidomics Compatible with Multiple Mass Spectrometry Platforms. Issue 1 (16th February 2018) - Herzog, Ronny; Schwudke, Dominik; Shevchenko, Andrej
Abstract: LipidXplorer is an open‐source software kit that supports the identification and quantification of molecular species of any lipid class detected by shotgun experiments performed on any mass spectrometry platform. LipidXplorer does not rely on a database of reference spectra: instead, lipid identification routines are user defined in the declarative molecular fragmentation query language (MFQL). The software supports batch processing of multiple shotgun acquisitions by high‐resolution mass mapping, precursor and neutral‐loss scanning, and data‐dependent MS/MS lending itself to a variety of lipidomics applications in cell biology and molecular medicine. Curr. Protoc. Bioinform . 43:14.12.1‐14.12.30. © 2013 by John Wiley & Sons, Inc.